EFFECTIVENESS OF ACCOUNTABILITY AND TRANSPARENCY OF BOS FUND MANAGEMENT USING THE ARKAS APPLICATION - Sahdan (Universitas Nurul Jadid, 2023)
One of the government's policies in supporting the advancement of education is to provide educational assistance in the form of school operational assistance funds (BOS). In managing BOS funds so that they can run optimally, good financial management skills are needed for schools. The method used in this research is qualitative with descriptive analysis. Sources of information were obtained from various stakeholders such as school principals, treasurers, and teachers at MAS Ulumuddin Lhokseumawe. Data collection was carried out through interviews, documentation, and literature review. The results showed that there was an increase in efficiency and effectiveness in the accounting system for the use of BOS funds after using the school activity plan and budget application (ARKAS). The effectiveness, accountability and transparency of the management of BOS funds using the ARKAS application in the activity plan and school budget at MAS Ulumuddin Lhokseumawe are interrelated and have been running very well and optimally.